Appraisal of public policy on conflict resolution for harmonious industrial relations practice in Nigeria (2002)
This paper examines policy on conflict resolution for harmonious industrial relations practice in a deregulated economy with reference to Nigeria. This deregulation of industrial relation in the public service sector stems from the civil service re-organization Decree (no. 43) of 1988. The policy regulation stipulates that the relevant trade unions should henceforth negotiate with each state and local governments over its terms and conditions of employment having in mind the government ability to “pay”. Unfortunately there is usually the problem of double standard on the part of government in the implementation of the policy. This double standard thus provides avenue for conflict (s) in the industrial relation systems. This is on the account that deregulation policy provides that, one industrial union at the federal, state and local government should negotiate separately on the same issues, the same government policy, having or-ganised the trade unions along industrial lines, had insisted that collective bargaining should be effected in the public sector through national joint industrial council. This contradiction in policy direction has made industrial environment. Our position in this paper is that much a deregulated industrial system is the best process for ensuring industrial harmony, government policy on this should be consistent. For example, the fixing of basic minimum wage at any level of public work should not be accommodated; otherwise, conflicts and other obstacles in industrial pace will continue to mar the peace of industrial relations practice in Nigeria. However, conflicts as a force of balance of power cannot be completely avoided, or eliminated. Hence, this paper provides strategies for nipping in bud contentious issues that may lead to conflict with regard to the administration of policy.